Reviewing risk process integration effectiveness into Malaysia landscape architecture project lifecycle - S.Muthuveeran, Adam Aruldewan; Mohd Tahir, Osman; Ibrahim, Roziya; Abd-Karim, Saipol Bari (e-International Publishing House, 2020)
This paper explores the effectiveness of risk process integration into landscape architecture project lifecycles, a subject that found to be lacking in risk management studies. The fieldwork of data collection conducted through structured interviews as well as document reviews from three completed landscape architecture projects in Klang Valley, Malaysia. The collected data analysed using content and thematic analysis. The research found that the risk process ineffectively integrated into project lifecycle with results presenting incomplete process, unplanned and redundant activity flows. The study suggests that common practice constrains practical risk management application that then restrains its benefit realisation.